Impact of Pilates exercises on the muscular ability and components of jumping to volleyball players - Lotfy El-Sayed, S.; Salah-Eldin Mohammed, M.; Farouk Abdullah, H. (World Journal of Sport Sciences, 2010)
This study is regarded a methodological attempt to identify the impact of Pilates exercises on the muscular ability and components of jump on Volleyball Players. Researchers have noticed the low level in skill performance and their endurance to continue the performance in a good way particularly in matches that are approximately similar in level. So, researchers tended to use Pilates exercises to identify their impact on raising muscular ability level and components of jump simultaneously. The experimental approach was applied on a sample of 20 players of eastern company sportive club in Arab Republic of Egypt, their ages ranged between 18 and 20. One of the most important results of this research was the improvement in muscular ability level of legs in the posterior measurement than the prior one by 12.04%. Also, there is an improvement in jump components. The improvement percentage of the jump height was by 12.58%. As of the flying time, it was 7.86%. As for the power, there was a decrease in level by-11.71%. Contact time decreased in the prior measurement by-5.50% than the posterior one. As for biological capacity variable, there was an improvement estimated by 12.86% in posterior measurement than prior one. There was an improvement in attack performance by 10.06% and it was 20.94% in the block.